An exploration of person-centred concepts in human services: A thematic analysis of the literature. Issue 10 (October 2017) - Waters, Rebecca A.; Buchanan, Angus
Highlights: The current understanding of person-centredness facilitates further misunderstanding and misinterpretation. The review indicates that a key reason why person-centredness covers such a wide terrain is because conceptualisations and developments in person-centredness have evolved within their policy spheres which have been largely siloed. This siloed development of understanding person-centredness has contributed to a wide range of conceptualisations making it resistant to narrowing understanding and subject to inconsistent measurement or operationalisation. The review suggests that there are key points of overlap despite this siloed development which may contribute to a joint conceptualisation. Further research on application and service expressions of being 'person-centred' is necessary. Abstract: Being 'person-centred' in the delivery of health and human services has become synonymous with quality care, and it is a core feature of policy reform in Australia and other Western countries. This research aimed to identify the uses, definitions and characteristics of the term 'person-centred' in the ageing, mental health and disability literature. A thematic analysis identified seven common core themes of person-centredness: honouring the person, being in relationship, facilitating participation and engagement, social inclusion/citizenship, experiencing compassionate love, being strengths/capacity focussed, and organisational characteristics. These suggest a set of higher-order experiences for people that are translated differently in different human services. There is no common definition of what it means to be person-centred, despite being a core feature of contemporary health and human service policy, and this suggests that its inclusion facilitates further misunderstanding and misinterpretation. A common understanding and policy conceptualisation of person-centredness is likely to support quality outcomes in service delivery especially where organisations work across human service groups. Further research into the application and service expressions of being 'person-centred' in context is necessary.